Alirocumab Treatment and Achievement of Non‐High‐Density Lipoprotein Cholesterol and Apolipoprotein B Goals in Patients With Hypercholesterolemia: Pooled Results From 10 Phase 3 ODYSSEY Trials. Issue 8 (August 2017) - Bays, Harold E.; Leiter, Lawrence A.; Colhoun, Helen M.; Thompson, Desmond; Bessac, Laurence; Pordy, Robert; Toth, Peter P.
Abstract : Background: Non‐high‐density lipoprotein cholesterol (non‐HDL‐C) and apolipoprotein (apo) B are better predictors of atherosclerotic cardiovascular disease risk than low‐density lipoprotein cholesterol alone. US and European lipid management guidelines support non‐HDL‐C and apoB as targets for lipid‐lowering therapy. Methods and Results: This analysis evaluated the efficacy of alirocumab, a proprotein convertase subtilisin/kexin type 9 inhibitor, on non‐HDL‐C and apoB. Data were derived from 4983 patients enrolled in 10 randomized, placebo‐ or ezetimibe‐controlled Phase 3 ODYSSEY trials. Primary end point for this pooled analysis was percent reduction in non‐HDL‐C and apoB at Week 24; secondary end points included the percentage of patients achieving guideline‐directed treatment goals (National Lipid Association guidelines: non‐HDL‐C <100 or <130 mg/dL for patients at very high and high cardiovascular risk, respectively; European Society of Cardiology/European Atherosclerosis Society guidelines: apoB <80 mg/dL for patients at very‐high cardiovascular risk). Data were grouped according to comparator, alirocumab starting dose, and concomitant statin use. Compared with controls, alirocumab produced significantly greater reductions in non‐HDL‐C and apoB at Week 24 ( P <0.0001), an effect extending up to 78 weeks. More alirocumab‐treated patients achieved levels of non‐HDL‐C <100 mg/dL and apoB <80 mg/dL ( P ≤0.0001 versus control). By Week 24, >70% of alirocumab‐treated patients on background statin achieved non‐HDL‐C <100 or <130 mg/dL, and apoB <80 mg/dL. Safety was comparable across pooled groups and in line with previous reports. Conclusions: Alirocumab produced significant, sustained reductions in non‐HDL‐C and apoB, allowing more patients to achieve lipid goals compared with placebo or ezetimibe and irrespective of maximally tolerated statin use.